BALANCING LOCAL BUDGETS UNDER THE CONDITIONS OF FINANCIAL DECENTRALIZATION - V.V., Mamonova; O.O., Vasyleha (Pressing Problems of Public Administration, 2016)
Grounded theoretical and methodological approaches and formed recommendations for balancing the local budgets during the  nancial decentralization. Among them – the introduction of the compensator of the corporate income tax in the form of interbudgetary transfer; amend the legislation governing to gathering of excise tax; execute expenditures on training of workers in vocational schools  nanced from the state budget; streamline the compensation mechanism for preferential thoroughfare some categories of citizens.